2009
DOI: 10.2486/indhealth.47.469
|View full text |Cite
|
Sign up to set email alerts
|

Individual Susceptibility to Occupational Contact Dermatitis

Abstract: Occupational Contact Dermatitis (OCD) is one of the most common work-related diseases. High risk occupations are in health care, hairdressing, food sector and metal industry. OCD tends to become chronic; persistent OCD often results in impaired quality of life and loss of work ability. The purpose of this article is to review the present knowledge on the factors which determine individual susceptibility to acquire OCD. Recent discoveries regarding genes involved in the skin barrier, inflammatory response and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 89 publications
4
48
2
4
Order By: Relevance
“…However, the impact of atopy on the development and course of CS and ACD is still controversial. There are studies that have not found any relation between atopy and CS [4,11], while other studies pointed out atopy as a predictor of poor ACD prognosis [12]. On the other hand, a certain number of studies indicated that severely expressed atopic diseases protected from the development of CS [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the impact of atopy on the development and course of CS and ACD is still controversial. There are studies that have not found any relation between atopy and CS [4,11], while other studies pointed out atopy as a predictor of poor ACD prognosis [12]. On the other hand, a certain number of studies indicated that severely expressed atopic diseases protected from the development of CS [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…the degree of exposure to relevant contact allergens including their concentration and duration of exposure, thus making occupational exposures highly important [3]. On the other hand, recent studies have indicated the potential involvement of certain genetic factors in the development of ACD, such as polymorphisms of genes encoding proinflammatory cytokine TNFA-308, filaggrin (FLG) and claudin-1 [4,5,6]. However, the influence of these gene polymorphisms has not yet been clearly established, and the impact of FLG mutations has been shown for the development of nickel ACD [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This special issue of Industrial Health, "Individual Susceptibility to Occupational Hazard", deals with the individual variability in the effects of various occupational factors including nine articles which refer to chemical [15][16][17][18] , psychosocial [19][20][21] , biological 22,23) and physical factors 24) . The articles regarding chemical factors include a systematic review by Julvez and Grandjean on neurodevelopmental toxicity 15) .…”
mentioning
confidence: 99%
“…The exposure to chemicals in early developmental stage is an important issue in occupational health, because the substantial vulnerability of the developing nervous system to low concentrations of neurotoxic chemicals should lead to a strengthened emphasis on protection of pregnant workers and women in general against substances that may cause harm to the fetus. Another review article by Kezic et al 16) discuss the individual susceptibility to occupational contact dermatitis. They conclude that recent discoveries on genes involved in the skin barrier, inflammatory response and biotransformation of xenobiotics provide more insight in the individual susceptibility for occupational contact dermatitis, and that knowledge of the factors which predispose to this disease is useful for the application of preventive measures and for career guidance for apprentices and workers.…”
mentioning
confidence: 99%